Motivation in Adult Education: From Engagement to Performance - Prof. Philippe Carre (Adult Education Research Conference, 2000)
This paper will focus on recent developments on the theme of adult motivation for education and training. It is based on the results of a large empirical research project conducted in France between 1997-99 .